A Continuing Care Program at Home on Caregiver’s Role for Children with Congenital Heart Disease: A Pilot Study - Wangsawat, Tidarat; Chemama, Nisreen; Hayee, Fusiyah; Jehloh, Latifah; Jaisomkom, Anyapaksorn; Tongnuang, Patcharawadee; Hayeese, Wanisa; Kuiburd, Thussaneeya; Pratiwi, Hikmi Muharromah (Jurnal Keperawatan Soedirman, 2024)
Caregivers should have adequate caring roles knowledge of children to increase the quality of life of children with congenital heart disease (CHD). Aim: To develop and evaluate the effect of a home-based continuing care program on the role of caregivers for children with CHD. This pilot study was a quasi-experiment with one group pre-posttest without control group design and conducted between October 2018 and September 2019 in Narathiwat, Pattani, and Yala. Thirty caregivers were recruited using a multistage random sampling technique. The program covered teaching, demonstration, and feedback equipped with a manual of CHD for six weeks. The self-developed caregiver role questionnaire was provided to evaluate caregiver care roles. The paired t-test was applied to evaluate the different scores of the caring roles before and after the program with the significant p value < 0.05. The scores of the caregivers’ roles for children with CHD after receiving the program were significantly higher than the scores before receiving the program (t = 6.20, p < .001). Continuing care programs enhance caring roles related knowledge of children with CHD. This program is recommended to apply continuously for caregivers of children with CHD at the outpatient or as part of discharge planning